Steered polymorphic nanodomains in TiO2 to boost visible-light photocatalytic oxidation. Issue 16 (28th March 2022) - Zhang, Zeju; Niu, Mang; Li, Wei; Ding, Chenfeng; Xie, Peitao; Li, Yongxin; Chen, Lili; Lan, Xiaopeng; Liu, Chunlei; Yan, Xiaodong; Fu, Xuewei; Liu, Yaochun; et al.
Abstract : A novel TiO2 -based composite material composed of in situ generated biomimetic polymorphic nanodomains including carbon nitride (C3 N4 ) and (001)-/(101)-faceted anatase nanocrystals is reported. Abstract : A breakthrough in enhancing visible-light photocatalysis of wide-bandgap semiconductors such as prototypical titania (TiO2 ) via cocatalyst decoration is still challenged by insufficient heterojunctions and inevitable interfacial transport issues. Herein, we report a novel TiO2 -based composite material composed of in situ generated polymorphic nanodomains including carbon nitride (C3 N4 ) and (001)/(101)-faceted anatase nanocrystals. The introduction of ultrafine C3 N4 results in the generation of many oxygen vacancies in the TiO2 lattice, and simultaneously induces the exposure and growth of anatase TiO2 (001) facets with high surface energy. The photocatalytic performance of C3 N4 -induced TiO2 for degradation of 2, 4-dichlorophenol under visible-light irradiation was tested, its apparent rate being up to 1.49 × 10 −2 min −1, almost 3.8 times as high as that for the pure TiO2 nanofibers. More significantly, even under low operation temperature and after a long-term photocatalytic process, the composite still exhibits exceptional degradation efficiency and stability. The normalized degradation efficiency and effective lifespan of the composite photocatalyst are far superior to other reported modified photocatalysts.